Pirates of the Sea++: A Serious Game for Computer Science Education - Cherry, Walker; Morsi, Rasha; Hacker, Desideria (IEEE Global Engineering Education Conference, 2025)
The primary focus of this work is to design and implement a 2D educational platformer game for Computer Science students, for deployment on the PC. In STEM education, 'gaming in education' has a great deal of promise since it can translate complex topics that are difficult to learn and master into fun and engaging lessons for students. While not new, video games are a powerful learning tool that still has a great deal of unused potential. Gaming offers the potential of reaching a wide range of people with diverse learning styles. Due to the inherent difficulty of teaching material in STEM fields, the need for more engaging ways to convey this information is vital to students. This work presents a solution to this problem through the implementation of an educational 2D platformer game. This game, Pirates of the Sea++, aims to teach students basic output structure, basic C++ data types, conditional operators, and conditional statements such as if statements and while loops. Pirates of the Sea++ is a 2D educational platformer game in which the player is an adventurer that is seeking a treasure that was hidden by a pirate. The pirate leaves behind clues in C++ code in their notebook, and the player will use his/her knowledge of C++ to decipher the code and obtain the treasure. The player navigates challenging platforming levels and later faces a series of problems that will assess their knowledge of C++ programming. The player will receive a score based on their performance in the game as well. Later, a detailed Human Subjects Protocol was developed and used to assess the educational and gaming aspects of Pirates of the Sea++ for use in classrooms in the future on a select group of volunteers who played and reviewed the game. Pirates of the Sea++ was entered into a serious games competition at the I/ITSEC Conference and won a Best Student Developed Game award.